Metaversia: a mooc model for higher education - Santos, Tiago (2013)
Globalization and economic interdependency of a post-modern society point toward an internationalization mission for the university. However, on a global scale, social, economic, and cultural circumstances have significant effects upon an individual’s ability to show the merit required in higher education. The growing open access movement reveals the early emergence of a meta-university that bring cost-efficiencies to institutions through the shared development of educational materials, which is particularly important to the developing world. But despite the huge success in the dissemination and democratization of knowledge provided by the open access movement, it has attached a severe financial downside, and configures a hamper in educational innovation due to its failure in harnessing Web 2.0 collaborative technologies. In order to find a model that better suits the needs of collaborative teaching and learning in a networked information economy, two approaches are followed in this dissertation. The first consists in the analysis and comparison of the open education ecosystem. On the other approach, based on the previous results, we propose a MOOC model, Metaversia, for a collaborative network that harness the capital exchange potential, and knowledge-building opportunities that rests on the connections between people, enabling citizen's full participation in the actual networked information economy.